ANALISIS KONTRIBUSI JARINGAN KOTA KREATIF UNESCO SEBAGAI INSTRUMEN SOFT POWER DALAM DIPLOMASI BUDAYA INDONESIA - Isma Triyana; Ni Made Priyamka A.P.S; Ario Bimo Utomo (Halu Oleo University, 2025)
This study analyses the contribution of the UNESCO Creative Cities Network (UCCN) as a soft power instrument in Indonesian cultural diplomacy. It is motivated by the increasing role of creative cities in Indonesia that are members of the UNESCO Creative Cities Network in strengthening cultural identity, promoting tourism, and expanding international networks. The purpose of this study is to understand how Indonesia's membership in the UNESCO Creative Cities Network can be utilised as a soft power instrument to improve Indonesia's image, influence, and position on the global stage. Overall, this study concludes that the UNESCO Creative Cities Network is effective as a soft power instrument in Indonesian cultural diplomacy, not only through the promotion of arts and culture, but also by positioning Indonesia as a creative, creative, and global partner. Closer collaboration between the government, the private sector, and the creative community is needed to maximise the benefits of UNESCO Creative Cities Network membership for sustainable development and future Indonesian diplomacy.